2011
DOI: 10.1071/rd10268
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between late embryonic mortality and the increase in plasma advanced oxidised protein products (AOPP) in dairy cows

Abstract: The involvement of protein oxidation in embryonic mortality (EM) has been poorly investigated in cows. Advanced oxidation protein products (AOPP) are markers of protein oxidation generated by activated neutrophils and involved in inflammation. The aim of this work was to study AOPP in cow plasma and their relationship with late EM. The outcomes of 158 artificial inseminations (AI) were examined in 72 cows, which were classified ex post on the basis of blood progesterone and pregnancy-associated glycoprotein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 47 publications
3
30
2
3
Order By: Relevance
“…In humans, AOPP increase has been associated with several immuno-inflammatory markers and they have been proposed as an exquisite marker of OS correlating with monocyte activation (Witko-Sarsat et al 1998). The prolonged half-life of AOPP allows an indirect reflection of the intensity of the OS (Santulli et al 2013) and has been reported to be elevated in dairy cows with embryonic mortality (Celi et al 2011). The AOPP level was elevated at 9 h and this may have been associated with the development of the cyst in cow 1258; however, this cannot be concluded definitively from the results of this study.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…In humans, AOPP increase has been associated with several immuno-inflammatory markers and they have been proposed as an exquisite marker of OS correlating with monocyte activation (Witko-Sarsat et al 1998). The prolonged half-life of AOPP allows an indirect reflection of the intensity of the OS (Santulli et al 2013) and has been reported to be elevated in dairy cows with embryonic mortality (Celi et al 2011). The AOPP level was elevated at 9 h and this may have been associated with the development of the cyst in cow 1258; however, this cannot be concluded definitively from the results of this study.…”
contrasting
confidence: 56%
“…It is plausible that OS plays a crucial role in the cause and progression of a number of reproductive events and can influence the reproductive axis at different levels. For example, previous studies have shown that OS is associated with embryonic loss (Celi et al 2012;Celi et al 2011) and that OS has a role in the pathogenesis of follicular cystic ovarian disease (Rizzo et al 2009). Therefore, the objective of this study was to examine the plasma concentration of progesterone and OS biomarkers that were measured in cow 1285 diagnosed with an ovarian follicular cyst.…”
mentioning
confidence: 99%
“…Albumin is a free radical scavenger but it is also the predominant oxidised protein contributing to AOPP formation (Celi, 2011b). Indeed, concentrations of AOPP can be associated with embryonic losses and are considered an indicator of inflammation and oxidative stress in dairy cows (Celi et al, 2011(Celi et al, , 2012. The lack of differences in albumin and AOPP concentrations between HG and FL affected rams may reflect the mild level of lesions observed in this study.…”
Section: Discussionmentioning
confidence: 85%
“…EM and P groups showed similar levels of MDA. Celi et al (2011) observed an increase in MDA concentrations in dairy cows suffering from late embryonic mortality (on 45 and 60 days after AI). These differences could be related to the different times when embryo mortality occurred.…”
Section: Discussionmentioning
confidence: 90%